THE IMPLEMENTATION OF A SOCIAL MEDIA ANALYTICS TOOL ‘SOCIAL BEARING’ TO COMPREHEND FOREIGN PROPAGANDA RELATED TO PAPUAN SEPARATIST ISSUES - M. Yusuf Samad; Richardus Eko Indrajit (The Republic of Indonesia Defense University, 2022)
Foreign intervention in interfering with domestic affairs is a violation of international law. The intervention was in the form of massive propaganda about Papuan separatists carried out on social media Twitter so an analytical tool was needed that made it easier to understand propaganda by foreign parties. The purpose of this study is to determine the implementation of social media analysis tools in the form of Social Bearing to understand foreign propaganda related to the Papua issue. This research is qualitative research using Modern Propaganda Theory. The results showed that Twitter account propaganda could be identified easily through the use of the Social Bearing analysis tool so that the @FreeWestPapuaNL account propaganda techniques and techniques could be identified and visible in the 11 results of the Social Bearing analysis, the account used pervasive propaganda methods while the propaganda techniques were Testimony and Card Stacking. These propaganda methods and techniques constitute a violation of international law due to foreign intervention in Indonesia's internal affairs. For this reason, Indonesia must reaffirm at international forums that the Papua problem is a domestic problem for Indonesia. In addition, foreign parties massively spread content about Papuan separatists, both from their tweets and by sharing tweets from other Twitter accounts. The use of separatist issues is more massive when there are moments that are closely related to the Papuan separatist issue